Radar Meteor - Raka Ahmad Saputra; Kiki Alfiansyah; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Meteorologists can gain a lot of useful information by using radar qualitatively, quantitative measurements can be very useful. However, these values are generally five times lower than values calculated from radar theory, and there is no satisfactory explanation for these differences. The article derives the radar equation for meteorological purposes, paying special attention to the effects of the shape of the main lobe of the beam and its outer radiation. It can be seen that the previous theoretical expressions for the gain and echo strength are too large and therefore the previous equations overstate the received power. This equation matches all experimental data so that later this system is very suitable to be implemented in Android apps that are used by the community.